Severe gut mucosal injury induces profound systemic inflammation and spleen-associated lymphoid organ response - Wang, Xiao; Du, Chao; Subramanian, Saravanan; Turner, Lucas; Geng, Hua; Bu, Heng-Fu; Tan, Xiao-Di (Frontiers in Immunology, 2024)
Clinical evidence indicates a connection between gut injuries, infections, inflammation, and an increased susceptibility to systemic inflammation. Nevertheless, the animal models designed to replicate this progression are inadequate, and the fundamental mechanisms are still largely unknown. This research explores the relationship between gut injuries and systemic inflammation using a Dextran Sulfate Sodium (DSS)-induced colonic mucosal injury mouse model. Continuous treatment of adult mice with 4% DSS drinking water yielded a remarkable mortality rate by day 7, alongside intensified gut injury and detectable peripheral inflammation. Moreover, RNAscope in situ hybridization with 16S rRNA probe noted bacterial penetration into deeper colon compartments of the mice following treatment with DSS for 7 days. Histological analysis revealed inflammation in the liver and lung tissues of DSS-treated mice. In addition, we found that DSS-treated mice exhibited elevation of Alanine transaminase (ALT) and Aspartate transaminase (AST) in peripheral blood and pro-inflammatory cytokine levels in the liver. Notably, the DSS-treated mice displayed a dampened metabolic profile, reduced CD45 marker expression, and an increase in apoptosis within the lymphatic organ, like the spleen. These findings suggest that high-dose DSS-induced gut injury gives rise to sepsis-like systemic inflammation characterizing multiple organ injury and profound splenocyte apoptosis and dysfunction of CD45+ cells in the spleen, indicating the role of the spleen in the pathogenesis of gut-derived systemic inflammation. Together, the severe colonic mucosal injury model facilitates research into gut damage and associated peripheral immune responses, providing a vital framework for investigating mechanisms related to clinically relevant, gut-derived systemic inflammation.